PENGARUH SENAM ERGONOMIC TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI DUSUN BANGLE WILAYAH KERJA PUSKESMAS TAMBAKREJO JOMBANG - Faridl, Faridl Zainal Abidin; Dina camelia; Sudarso (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Hypertension is a condition of increased systolic blood pressure of more than 140 mmHg and diastolic pressure of more than 90 mmHg. Objective: This study aims to determine the effect of ergonomic exercise on changes in blood pressure in elderly people with hypertension in Bangle Hamlet, working area of Tambakrejo Public Health Center, Jombang. Method: This study used a pre-experimental one-group pretest-posttest design. The population was 30 elderly people with a sample size of 22 respondents selected through purposive sampling according to the inclusion criteria. The exercise was carried out 6 times in 2 weeks, the instrument used was an aneroid sphygmomanometer, and the analysis was performed using the Wilcoxon signed-rank test. Result: The results showed a change in blood pressure from the percentage of grade II hypertension in the pretest of 45.5% and after the ergonomic exercise intervention in the posttest decreased to 13.6%. When tested using the Wilcoxon signed-rank test, the value obtained was = 0.001, less than (p < 0.05). Conclusion: Ergonomic exercise can lower blood pressure in elderly people with hypertension, indicating that this therapy is an effective nonpharmacological method. The clinical implication of this finding is the importance of applying ergonomic exercise regularly to manage blood pressure in the elderly and prevent cardiovascular complications.